Pengembangan E-Magz Fisika Untuk Meningkatkan Literasi Sains Peserta Didik SMA Pada Materi Medan Magnet - Dewanto Kamas Utomo; Yuvita Oktarisa (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2022)
One of the factors that cause high school students did not achieve optimal physics learning outcomes because teaching materials that still less interactive. This non-interactive teaching material was one of the causes of the low scientific literacy ability of high school students. This study aims to develop teaching materials in the form of e-magz on magnetic field materials at SMAN 1 Serang City. This study uses the ADDIE development model. Product validation is carried out by experts using a questionnaire. The average validation results for the material are 94% (very feasible) and for media 96% (very feasible). The results of the pre-test and post-test test scores show an n-gain value of 0.73 (high). These results are supported by the data on the responses of students with very good categories to the assessment of e-magz teaching materials with a percentage of 84.7%. Therefore, the results of the development of e-magz teaching materials are appropriate to be used as supporting teaching materials to improve scientific literacy.